Developing the guided inquiry-based module on the circulatory system to improve student's critical thinking skills - Dynna Sri Wulandari; Baskoro Adi Prayitno; M. Maridi (University of Muhammadiyah Malang, 2022)
The limitations of inquiry-based teaching modules impact the low critical thinking skills of students. The research objective is to develop an inquiry-based module to improve students' critical thinking skills. This development research uses the Borg and Gall model in designing and testing the module. The development was carried out in February - November 2020 at Batik Senior High School 1 of Surakarta, Central Java. The subjects of this study were students of class XI-Science Batik Senior High School 1 of Surakarta. The assessment of the feasibility and effectiveness of the module uses a validation instrument by linguists, material experts, and learning experts. Assessment of students' critical thinking skills using HOTS questions. The effectiveness of the module was tested using the Z test. The results concluded that the module was feasible to use in learning with a feasibility score of 3.83 (linguistic aspect), 3.92 (material aspect), and 3.80 (learning aspect). Furthermore, this module effectively improves students' critical thinking skills as indicated by the results of the Z test (α<0.05). This study recommends the development of inquiry-based modules in improving students' critical thinking skills.